Business ethics in Islam - Ali, Abbas, 1953- (Edward Elgar, 2014)
Drawing on original sources found in the first century of Islam and guided by contemporary developments in the field of business ethics, this book offers Islamic perspectives on ethical conduct in the marketplace: what organizations and other market actors do to deal with monumental challenges in today's market